Effects of Temperature on the Filtration Characteristics of a Dual‐Layer Granular Bed Filter. Issue 9 (25th July 2018) - Shen, Wei-Jie; Yang, Guo-Hua; Liu, Peng; Yao, Zhi-Wei; Shi, Hua-Jie; Cui, Yu-Yong; Li, Zhen
Abstract: The effects of temperature on the filtration efficiency and pressure drop of a dual‐layer granular bed filter were investigated in a hot dual‐layer granular bed filter with experimental dust. Enhanced higher filtration efficiency was obtained with higher filtration temperature, and the removal efficiency of ultrafine dust was also at a high level. Simultaneously, the total pressure drop maintained at an acceptable range. The results demonstrate that the dual‐layer granular bed has excellent prospects for application to low‐temperature coal pyrolysis. Abstract : The impact of temperature on the filtration efficiency and pressure drop of a dual‐layer granular bed filter in a hot dual‐layer granular bed filter with experimental dust was evaluated. Higher filtration temperatures improved the filtration efficiency and the removal efficiency of ultrafine dust. The dual‐layer granular bed has excellent potential for application to low‐temperature coal pyrolysis.